The development of a linear cutting machine used to characterise fem modelling parameters for cutting ug2 reef - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2024)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2024.